'I don't even know how to start that kind of conversation': HIV communication between mothers and adolescents with perinatally acquired HIV. (September 2020) - Gibbs, Caroline; Melvin, Diane; Foster, Caroline; Evangeli, Michael
Young people with perinatally acquired HIV are now surviving into late adolescence and adulthood. We explored HIV communication within mother/adolescent dyads following naming of the adolescents' HIV. Five adolescents with perinatally acquired HIV (14–16 years) and their biological mothers were interviewed separately. HIV communication between mothers and children was rare. Discussion most commonly related to biomedical aspects of HIV. Onward HIV disclosure was discouraged by mothers, which often contrasted with adolescents' beliefs. Discussing emotional and sexual aspects of HIV was mutually avoided. Culturally sensitive support and guidance should be offered to families about discussing HIV, considering potentially differing perspectives.